The role of leadership on employee mental health in geographically isolated and non-isolated workplaces: A systematic review and meta-analysis. ... - MISS Jasmine Bhatia; Crane, Monique (OSF Registries, 2023)
Geographically isolated or remote occupational contexts present unique job demands that may amplify the effects of the workplace on employee mental health (Palinkas & Suedfeld, 2021). These workplaces are operationalised according to the location, time or nature of work activities undertaken while distanced from the assistance of rescue, medical and emergency services, where communication is limited, and where travel is difficult (Comcare, 2013). Examples include mining, at-sea Navy deployments or submarines, Arctic and Antarctic explorations/expeditions and spaceflight (Milne & Bahn, 2015; Palinkas, 2003). Under these conditions, psychosocial issues can arise from the complexities of living in confined spaces, shift work and prolonged distance from family with limited communications (Brasher, et al., 2010). Additionally, the blurring of boundaries between work and off-work time may be conducive to psychological risks, particularly when there is inadequate opportunity for recovery (Hetland et al., ...